Serum Unconjugated Bile Acids and Small Bowel Bacterial Overgrowth in Pediatric Intestinal Failure: A Pilot Study. Issue 2 (23rd July 2018) - Galloway, David; Mezoff, Ethan; Zhang, Wujuan; Byrd, Melissa; Cole, Conrad; Aban, Inmaculada; Kocoshis, Samuel; Setchell, Kenneth DR; Heubi, James E
Abstract: Background : We determined qualitative and quantitative serum unconjugated bile acid (SUBA) levels among children with history of intestinal failure (IF) and suspected small bowel bacterial overgrowth (SBBO). Methods : This was a single‐center, case‐control pilot study conducted at Cincinnati Children's Hospital Medical Center. Children with history of IF and suspected SBBO were enrolled as subjects. Age‐matched children without IF or suspected SBBO served as controls. All participants underwent small bowel fluid sampling for microbial culture analysis. Additionally, serum fractionated and total bile acids were measured by liquid chromatography‐mass spectrometry at enrollment and following treatment for SBBO. Results : SUBA concentrations were elevated in IF subjects (median 1.16 μM, range 0.43–10.65 μM) compared with controls (median 0.10 μM, range 0.05–0.18 μM, P = 0.001). Among SUBA, chenodeoxycholic acid (CDCA) was significantly elevated in subjects (median 0.8 μM, range 0–7.08 μM) compared with controls (median 0 μM, range 0–0.03 μM, P = 0.012). When controls were excluded from analysis, IF subjects with positive aspirates for SBBO demonstrated higher concentration of CDCA (median 7.36 μM, range 1.1–8.28 μM) compared with IF subjects with negative aspirates (median 0.18 μM, range 0–1.06 μM, P = 0.017). Treatment for SBBO did not alter SUBA concentration. Conclusions : SUBA concentrations are elevated in children with history of IF and presumed SBBO compared with non‐IF controls. CDCA was more prevalent in IF subjects with positive aspirates for SBBO compared with IF subjects with negative aspirates. The determination of SUBA concentration may be a useful surrogate to small bowel fluid aspiration in the diagnosis of SBBO in children with history of IF.